Surgical intervention of a fibular sStress fracture in a male basketball player: A case report - Meador, R. G.; Randolph, T. L.; Balcik, B. J.; Hubbard, D. F.; McDonough, B. (International Journal of Athletic Therapy & Training, 2024)
This is a case of a 21-year-old male, African American Division I basketball player with a fibula stress fracture. The athlete initially reported pain, without distinct injury and was diagnosed with a stress fracture. After a short period of immobilization in a walking boot, this individual opted to undergo surgical intervention consisting of an intramedullary screw inserted in his left fibula. This was in consultation with the orthopedic team physician and orthopedic trauma surgeon. After a brief period of rest and continued immobilization in a walking boot, weight bearing as tolerated, the patient was able to start rehabilitation. He continued rehabilitation and progressive return to activity and was able to return to limited practice approximately 4 weeks. He played 13 min of a game in under 5 weeks (31 days). Stress fractures are not uncommon in basketball players, but a fibula stress fracture is one not often seen, and there is a paucity of data in the literature regarding this injury. A nonoperative approach to treatment of a fibula stress fracture typically yields good results but may lead to longer return than a surgical intervention. Providing athletes options for treatment may result in a quicker recovery. This case demonstrates a novel treatment option resulting in a quicker return to play.